Quantized non-adiabatic coupling terms to ensure diabatic potentials - Baer, Michael (2000)
A way to derive rigorous diabatic potentials from non-adiabatic coupling terms (NACTs) was suggested some time ago [M. Baer, Chem. Phys. Lett. 35 (1975) 112]. This approach could be applied only for cases when the NACTs are regular throughout configuration space. In this work a criterion is established to be fulfilled by NACTs which yields continuous and uniquely diabatic potentials defined throughout configuration space. It is found that this requirement leads to a kind of [`]quantization' with regard to the non-regular NACTs. A two-state model and a three-state model were considered as examples.